(untitled) (Research, Society and Development, 2022)
Objective: to evaluate the clinical effectiveness of different local drug delivery systems as adjuvants in periodontal and peri-implantis treatments, through a literature review. Methodology: a search was carried out in the "PubMed" and "Medline" databases, using the following descriptors: (1) Devices: "(PERIOCHIP) OR (ACTISITE) OR (ATRIDOX) OR (ARESTIN) OR (PERIOSTAT) OR (FBP) OR (CHLORHEXIDINE) OR (ELYZOL) OR (DENTOMYCIN) OR (CHLO-SITE)”; (2) Usage and effectiveness: “(PERIODONTAL) OR (CLINICAL OUTCOME) OR (CLINICAL RELEVANCE) OR (CLINICAL PERFORMANCE) OR (COADJUVANT TREATMENT)”; (3) Characterizers: “(INTRAPOCKET TECHNOLOGY) OR (SUPORTIVE PERIODONTAL THERAPY) OR (LOCAL DRUG DELIVERY) OR (CONTROLLED RELEASE)”; and, (4) Pathologies: "(PERIODONTAL DISEASE) OR (PERIODONTITIS) OR (PERI-IMPLANTITIS) OR (PERIODONTAL POCKET) OR (PERIODONTAL INFECTIONS)". The groups were added with the Boolean operator “AND”, to find the different intersections of descriptors that represented the proposed theme with greater precision. Results: 286 results were initially found, after removal of letters to authors, repeated articles and ARTICLES prior to 2006. The analysis of titles, "abstracts" and full texts was continued, and 9 articles were selected. Conclusion: Local drug delivery systems, as adjuvants to periodontal treatment, showed, mostly, promising results when compared to scaling and root planing isolated. In the clinical findings of peri-implantitis, further studies are necessary.